Alternative Splicing of FOXP3—Virtue and Vice - Mailer, Reiner K. W. (Frontiers in Immunology, 2018)
FOXP3 is the lineage-defining transcription factor of CD4+CD25+ regulatory T cells. While many aspects of its regulation, interaction and function are conserved among species, alternatively spliced FOXP3 isoforms are expressed only in human cells. This review summarizes current knowledge about alternative splicing of FOXP3 and the specific functions of FOXP3 isoforms in health and disease. Future perspectives in research and the therapeutic potential of manipulating alternative splicing of FOXP3 are discussed.